(untitled) (Quinto Sol, 2013)
The purpose of this article is to discuss some theoretical and methodological problems concerning the history of justice. The point of departure is my earlier work on the local legal culture of a rural district in the province of Buenos Aires (La paz del trigo). After reviewing the literature on legal historiography in Latin America, the article summarizes the main statements in that work. Then, it discusses some theoretical and methodological issues confronting legal historians, and suggests some lines of inquiry for future research.